1 Peter - Jobes, Karen H. 1952- (Grand Rapids Baker Academic, 2022)
A leading evangelical biblical scholar offers a substantive evangelical commentary on 1 Peter in the award-winning BECNT series.
Intro -- Half Title Page -- Series Page -- Title Page -- Copyright Page -- Dedication -- Contents -- Series Preface -- Author's Preface to the Second Edition -- Author's Preface to the First Edition -- Abbreviations -- Transliteration -- Map -- Introduction to 1 Peter -- I. A Greeting to the Christian Diaspora of Asia Minor (1:1-2) -- II. The Opening of the Letter: Reassurance for God's People (1:3-2:10) -- A. Doxology as the Basis for the Christian Life (1:3-12) -- 1. The Opening Doxology (1:3-5) -- 2. Joy and Suffering in the New Life (1:6-9) -- 3. The Christian's Advantage over the Prophets and Even the Angels (1:10-12) -- B. Be What You Are (1:13-2:3) -- 1. Be Children of the Father (1:13-21) -- 2. Christian Love Means Moral Transformation (1:22-2:3) -- C. The Identity of God's People (2:4-10) -- 1. A Spiritual House and a Holy Priesthood (2:4-8) -- 2. Now You Are the People of God (2:9-10) -- III. As God's People, Live Godly Lives (2:11-4:11) -- A. Commendable Social Behavior as God's People (2:11-3:7) -- 1. Lifestyle Evangelism (2:11-12) -- 2. Submit Even to Pagan Authority (2:13-17) -- 3. Christ's Example in Society's Most Basic Unit (2:18-3:7) -- a. The Slave as the Paradigm for Believers (2:18-25) -- b. Instructions to Christian Wives and Husbands (3:1-7) -- B. The Inner Qualities of Righteous Living (3:8-12) -- C. Suffering Unjustly for the Name of Christ (3:13-4:11) -- 1. Suffering for Doing Good (3:13-17) -- 2. Christ's Victory over Unjust Suffering (3:18-22) -- 3. Living Out Christ's Victory in an Unbelieving World (4:1-6) -- 4. Living Out Christ's Victory in the Christian Community (4:7-11) -- IV. Consolation for the Suffering Flock (4:12-5:11) -- A. Final Thoughts about Suffering for Christ (4:12-19) -- B. Final Exhortations to the Community (5:1-11) -- 1. Christ Shepherds His Flock through the Elders (5:1-5).
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Kommentar